Using time-driven activity-based costing to measure customer profitability, An applied study in Al Narjis Company for Construction and Building - AL-mashkoor, Imad A.S.; Hadi, Alaa Safaa M. (Edelweiss Applied Science and Technology, 2024)
The purpose of this study is to Measuring Customer Profitability by Using Time-Driven Activity-Based Costing (TDABC) at Al Narjis Construction & Building Company. A case study was conducted in Al Narjis Construction & Building Company, in one of its factories consisting of five production lines for producing pipes of various sizes. Interviews, direct observations, and documentation collection were used to collect the data. The results showed that some customer segments that were profitable in the traditional accounting system used in the factory management were identified as unprofitable using the method (TDABC). Only one factory operating in the company was examined in this research paper. Therefore, further research should focus on implementing customer profitability measurement using TDABC in other factories within the company and abroad. Based on the results of the study, factory management is better able to understand the profitability of different customer segments and implement appropriate strategies. Furthermore, TDABC time equations are seen as providing factory management with an opportunity to achieve a better balance between the capabilities offered in the departments. There is limited research on measuring profitability in industrial companies in general. Therefore, this paper is unique in the sense that it analyses the use of TDABC systems in a real factory case and for the first time in Basra Governorate (Iraq).